Mystery train [videorecording (DVD)] - Jarmusch, Jim, 1953-; Jarmusch, Jim, 1953-; Kudoh, Youki, 1971-; Nagase, Masatoshi, 1966-; Hawkins, Screamin' Jay (Criterion collection, 2010)
Aloof teenage Japanese tourists, a frazzled Italian widow, and a disgruntled British immigrant all converge in the city of Memphis in hot pursuit of the elusive 'King' himself, Elvis!